Role of Endoplasmic Reticulum Stress in Learning and Memory Impairment and Alzheimer's Disease-Like Neuropathology in the PS19 and APP(Swe) Mouse Models of Tauopathy and Amyloidosis - Briggs, Denise Isabelle (eNeuro, 2017)
Emerging evidence suggests that endoplasmic reticulum (ER) stress may be involved in the pathogenesis of Alzheimer’s disease (AD). Recently, pharmacological modulation of the eukaryotic translation initiation factor-2 (eIF2α) pathway was achieved using an integrated stress response inhibitor (ISRIB). While members of this signaling cascade have been suggested as potential therapeutic targets for neurodegeneration, the biological significance of this pathway has not been comprehensively assessed in animal models of AD. The present study investigated the ER stress pathway and its long-term modulation utilizing in vitro and in vivo experimental models of tauopathy (MAPT P301S)PS19 and amyloidosis (APP(Swe)). We report that thapsigargin induces activating transcription factor-4 (ATF4) in primary cortical neurons (PCNs) derived from rat and APP(Swe) nontransgenic (nTg) and transgenic (Tg) mice. ISRIB mitigated the induction of ATF4 in PCNs generated from wild-type (WT) but not APP(Swe) mice despite partially restoring thapsigargin-induced translational repression in nTg PCNs. In vivo, C57BL/6J and PS19 mice received prolonged, once-daily administration of ISRIB. While the compound was well tolerated by PS19 and C57BL/6J mice, APP(Swe) mice treated per this schedule displayed significant mortality. Thus, the dose was reduced and administered only on behavioral test days. ISRIB did not improve learning and memory function in APP(Swe) Tg mice. While ISRIB did not reduce tau-related neuropathology in PS19 Tg mice, no evidence of ER stress-related dysfunction was observed in either of these Tg models. Taken together, the significance of ER stress and the relevance of these models to the etiology of AD require further investigation.